2010
DOI: 10.1038/cdd.2010.140
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-activated ROCK-1 allows erythroblast terminal maturation independently of cytokine-induced Rho signaling

Abstract: Stem cell factor (SCF) and erythropoietin are strictly required for preventing apoptosis and stimulating proliferation, allowing the differentiation of erythroid precursors from colony-forming unit-E to the polychromatophilic stage. In contrast, terminal maturation to generate reticulocytes occurs independently of cytokine signaling by a mechanism not fully understood. Terminal differentiation is characterized by a sequence of morphological changes including a progressive decrease in cell size, chromatin conde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…It is possible that these proteins are also involved in chromatin condensation in erythroid differentiation. In addition, caspase-3 also activates ROCK-1, which allows terminal erythroid differentiation in part through phosphorylation of myosin II light chain (Gabet et al, 2011). How caspase-3 coordinates the cleavage of nuclear membrane proteins with the activation of DNase and ROCK-1 would be interesting to explore.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that these proteins are also involved in chromatin condensation in erythroid differentiation. In addition, caspase-3 also activates ROCK-1, which allows terminal erythroid differentiation in part through phosphorylation of myosin II light chain (Gabet et al, 2011). How caspase-3 coordinates the cleavage of nuclear membrane proteins with the activation of DNase and ROCK-1 would be interesting to explore.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 During the development of erythroblasts, ROCK1 is activated by caspase-3-mediated cleavage, allowing terminal maturation through phosphorylation of the light chain of myosin II. 33 Granzyme B is a serine protease expressed in the granules of cytotoxic lymphocytes, basophils, mast cells, and VSMC. 34 Granzyme B induces inflammation by cytokine release and contributes to the extracellular matrix remodeling.…”
Section: Molecular Roles and Regulation Of Rho-kinase In The Cardiovamentioning
confidence: 99%
“…Recently, Gabet et al demonstrated the involvement of ROCK1 in terminal maturation of erythroid cells using ROCK inhibitors and by knockdown of ROCK1. 34 Although useful, these studies do not distinguish between the physiologic functions of ROCK1 and ROCK2, thereby underscoring the importance of these related family members in regulating different functions. Importantly, the physiologic role of ROCK in blood cells is poorly defined.…”
mentioning
confidence: 99%